Splendors and miseries of the brain love, creativity, and the quest for human happiness - Zeki, Semir (Wiley-Blackwell, 2009)
This work examines the elegant and efficient machinery of the brain, showing that by studying music, art, literature, and love, we can reach important conclusions about how the brain functions. It discusses creativity and the search for perfection in the brain; examines the power of the unfinished and why it has such a powerful hold on the imagination; discusses Platonic concepts in light of the brain; shows that aesthetic theories are best understood in terms of the brain; discusses the inherited concept of unity in love using evidence derived from the world literature of love; addresses the role of the synthetic concept in the brain (the synthesis of many experiences) in relation to art, using examples taken from the work of Michelangelo, Cezanne, Balzac, Dante, and others.
Includes bibliographical references and index
Keywords: Kunst; Brain -- Physiology; Concept -- Physiological aspects; Creative ability -- Physiological aspects; Love -- Physiological aspects; Brain -- physiology; Art; Concept Formation -- physiology; Creativeness; Love; Hirnfunktion; Physiologische Psychologie; Ästhetik; Begriffsbildung; Neurobiologie; Liebe; Kreativität; Glück